PEMBINAAN AKHLAK SISWA MELALUI KEGIATAN EKSTRAKURIKULER DI SD NEGERI 16 KOTA BANDA ACEH - Mamparisi Mamparisi; Suraiya (Jurnal Ikhtibar Nusantara, 2026)
This study aims to analyze the development of students’ moral character through diniyah extracurricular activities at SD Negeri 16 Banda Aceh. This research uses a qualitative approach with a descriptive research design. The research subjects consisted of the principal, five diniyah teachers, one homeroom teacher, and ten fourth-grade students. Data collection techniques included observation, interviews, and documentation. Data analysis employed the Miles and Huberman model, including data reduction, data display, and conclusion drawing.The results show that diniyah extracurricular activities are conducted daily after the Zuhr prayer until before Asr prayer. The activities include congregational prayer, Qur’an recitation, memorization of daily prayers, and learning of aqidah akhlak and basic worship practices. The development of students’ moral character is carried out through four main methods: habituation, role modeling, advice, and supervision. Habituation forms behavior through repeated practices, role modeling provides concrete examples, advice enhances moral and spiritual awareness, and supervision functions as both control and guidance.The findings indicate that diniyah activities have a positive impact on students’ moral development, including improved discipline, politeness, responsibility, and awareness in worship. These findings are in line with Al-Ghazali’s concept of moral education, which emphasizes riyadhah (training), ta’wid (habituation), mau’izhah (advice), and muraqabah (supervision). Therefore, diniyah extracurricular activities are proven to be effective in fostering students’ moral character from an early age.